Congenital hypothyroidism presenting as isolated macroglossia in a term neonate: A case report - Basani, Laxman; Aepala, Roja (Indian Journal of Child Health, 2018)
Macroglossia is a clinical condition in which the tongue protrudes beyond the teeth or alveolar ridge during resting posture, or there is an impression of a tooth on the lingual border with the mouth open. True macroglossia occurs in hypothyroidism, Beckwith–Wiedemann syndrome, and storage disorders. Apparent or pseudo macroglossia may result from neurological impairment of the tongue or a relatively small buccal cavity as in Pierre Robin syndrome and Down’s syndrome. Rarely, macroglossia is inherited as an autosomal dominant condition. A wide variety of primary conditions of the tongue can cause tongue enlargement, e.g., lingual thyroid, cysts, tumors, hemangioma, lymphatic malformations, and myositis. Symptoms associated with macroglossia include noisy breathing, stridor, snoring, and feeding difficulties. Although macroglossia is described in hypothyroidism, there are few publications on macroglossia presenting in the neonatal period. We report a case of congenital hypothyroidism presenting as isolated macroglossia at birth in a term neonate.